The gender wage gap in an online labour market: the cost of interruptions - Adams-Prassl, A (University of Oxford, 2021)
This paper analyses gender differences in working patterns and wages on Amazon Mechanical Turk, a popular online labour platform. Using information on 2 million tasks, I find no gender differences in task selection nor experience. Nonetheless, women earn 20% less per hour on average. Gender differences in working patterns are a statistically and economically significant driver of this wage gap. Women are more likely to interrupt their working time on the platform with consequences for their task completion speed. A follow up survey shows that the gender differences in working patterns and hourly wages are concentrated amongst workers with children.